(untitled) (International Journal of Sustainable Energy and Environmental Research, 2014)
Achieving sustainable solutions to today’s burning environmental problems like atmospheric pollution, waste management etc requires some effective long term result oriented actions. These can be correlated with energy resources generations and its uses. An understanding of laws of Physics particularly thermodynamics laws can help in providing a sustainable solution to these serious problems. This article discuss how efficient energy resources utilization is related to waste and environmental problems. The renewable energy appear to provide an effective solution to waste production and its management . The various laws of physics give an idea of their future energy utilization patterns. These laws do not offer complete solution to such waste production and environmental degradation but provide ways to minimize them to such an extent that it remains within the limit of human tolerance. This can also show that efficient and economic utilization of energy resources particularly renewable energy can results in sustainable solution to waste.